2012
DOI: 10.1097/mpg.0b013e318266aa9e
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and Histological Gastric Lesions in Children With Celiac Disease

Abstract: Gastritis is a common finding in children with CD and adolescents. In celiac subjects, CSG is the most frequently detected. Our data suggest the hypothesis that LG may be related to a longer exposure to gluten. The presence of GPCA may suggest the presence of an underlying autoimmune process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
0
17
1
4
Order By: Relevance
“…Chronic superficial gastritis is several times more frequent in CD patients than the prevalence of HP infection. Moreover, lymphocytic gastritis has been reported in pediatric CD subjects (Nenna et al, 2012). Potentially, it may influence the assessment of HP presence using UBT.…”
Section: Hs Apmentioning
confidence: 99%
“…Chronic superficial gastritis is several times more frequent in CD patients than the prevalence of HP infection. Moreover, lymphocytic gastritis has been reported in pediatric CD subjects (Nenna et al, 2012). Potentially, it may influence the assessment of HP presence using UBT.…”
Section: Hs Apmentioning
confidence: 99%
“…This study suggested that occurrence of lymphocytic gastritis might be related with long-term exposure to gluten. 5 In an Iranian study including 250 patients, it was investigated if CD was related with gastric anomalies. It was concluded that the clinical presentation of CD was not different in the subjects with H. pylori infection and histology was nonspecific and unhelpful even if the patient had positive serology.…”
Section: Discussionmentioning
confidence: 99%
“…U literaturi se često navodi prisustvo LG udruženog sa celijakijom (11,12,18,19). Prema Hjustonskoj dopuni Sidnejske klasifikacije, gastritis se klasifikuje na akutni (hemoragični, erozivni, difuzni), hronični i na specijalne forme gastritisa (reaktivni, radijacioni, limfocitni, granulomatozni, eozinofilni i drugi infektivni gastritisi).…”
Section: Diskusijaunclassified
“…Podudarne rezultate sa našom studijom, po pitanju učestalosti hroničnog superficijalnog gastritisa, su publikovali Nenna i sar. (18). U suprotnosti sa našim rezultatom je studija (17) koja nalazi da je prevalenca hroničnog superficijalnog gastritisa skoro identična u grupi oboljelih i grupi kontrola.…”
Section: Hp-hp+unclassified